WORK MOTIVATION, ORGANIZATIONAL ACTIVENESS, AND FIELDWORK PRACTICE: PREDICTORS OF WORK READINESS IN STUDENTS - Romadani, Mutiara Nur; Wahono, Puji; Wolor, Christian Wiradendi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The success rate of a university can also be measured from the level of readiness of its students in the world of work. The purpose of this study is to measure how much effect the experience of organizational activity, and the experience of implementing Field Work Practices accompanied by Work Motivation has on Student Work Readiness. This research method uses a quantitative approach and the data obtained is primary data using survey data collection with a sampling technique of proportional random sampling. The population used was undergraduate students of Office Administration Education, Faculty of Economics, Jakarta State University with a sample size of 232 people. The data collected was then processed using SmartPLS software version 3.0 using inner models, outer models and hypothesis testing. The findings of the study showed that work motivation had a significant positive effect on student Work Readiness. Organizational activity had a positive effect on work readiness. Field Work Practice had a positive and significant effect on Work Readiness. Simultaneously, work motivation, organizational activity, and field work practice also had an effect on work readiness.